Billy Graham - Pollock, John. (London : Hodder and Stoughton, 1966)
Portrait, head and shoulders, facing right.
Photo by Warren K. Leffler.
This record contains unverified data from "Famous People" reference aid.
U.S. News & World Report Magazine Photograph Collection.
Contact sheet available for reference purposes: USN&WR COLL - Job no. 15743